Inovasi Penguatan Literasi Digital di Kalangan Remaja Kota Tasikmalaya Dalam Mendukung Capaian SDGS 2030 - Fitrah Arya Ramadhan; Yuda Amri Setiadi; Ichsan Rahman Fauzi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Digital Education or Digital Literacy is one of the main keys to preparing future generations who will never escape the involvement of modern devices or gadgets, in order to educate the generation in facing the challenges of global change. Tasikmalaya is one of the regions and cities that is attractive for teenagers to be the subject of achieving SDGS or in Indonesian "Sustainable Development Goals" in 2023. This article aims to determine the level of Digital Literacy of the community around Tasikmalaya City, especially teenagers. As well as proposing opinions and breakthroughs in strengthening effective Digital Literacy to support the country's SDGS. This research also discusses the positive impact of increasing digital literacy in supporting the achievement of SDGs 2030, especially in terms of increasing access to education, improving life skills, and reducing social disparities. The research method used is a literature study by reviewing similar previous studies to collect the necessary and relevant data. The results show that innovative approaches that focus on empowering teenagers as agents of change, integrating digital literacy into the school curriculum, and effectively using information and communication technology (ICT) can increase teenagers' digital literacy.